Boys at Risk : A Gender Issue in the Caribbean Requiring a Multi-Faceted and Cross-Sectoral Approach - Orlando, María Beatriz; Lundwall, Jonna (World Bank, Washington, DC, 2012)
The Latin American and Caribbean region has made significant progress in some basic indicators of gender equality (access to education and health services and female labor force participation) and lags behind in others. However, a second generation of emerging issues suggests that, although women continue to be disadvantaged in a number of indicators, boys' underachievement in education and their participation as perpetrators and victims of violent crime require a new gender paradigm that includes male issues. Despite the traditional focus on female-related indicators, there is a clear gender dimension to the problems of at-risk youth, since young boys and girls engage in different kinds of risky behaviors and in different ways. Boys and girls also tend to engage differently with schools, communities, and the labor market. This implies that programs and policies need to be designed and implemented with different approaches and tools to benefit and to reach effectively both girls and boys.